2018
DOI: 10.1007/s00497-018-0327-4
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in woody perennial Citrus: an update on nucellar embryony and self-incompatibility

Abstract: Review on citrus reproduction. Citrus is one of the most important and widely grown fruit crops. It possesses several special reproductive characteristics, such as nucellar embryony and self-incompatibility. The special phenomenon of nucellar embryony in citrus, also known as the polyembryony, is a kind of sporophytic apomixis. During the past decade, the emergence of novel technologies and the construction of multiple citrus reference genomes have facilitated rapid advances to our understanding of nucellar em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 103 publications
0
35
0
Order By: Relevance
“…Since trifoliate orange is cross-compatible with citrus, it is naturally conceivable to cross them in order to produce coldtolerant progenies. Unfortunately, this traditional means is substantially impeded due to unique reproductive characteristics of the majority of citrus cultivars, including polyembryony, long juvenile period, high degree of heterozygosity and male/female sterility (Zhang et al, 2018). As an alternative strategy, genetic engineering has been increasingly demonstrated to act as an effective and efficient approach to generate transgenic plants with improved stress tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Since trifoliate orange is cross-compatible with citrus, it is naturally conceivable to cross them in order to produce coldtolerant progenies. Unfortunately, this traditional means is substantially impeded due to unique reproductive characteristics of the majority of citrus cultivars, including polyembryony, long juvenile period, high degree of heterozygosity and male/female sterility (Zhang et al, 2018). As an alternative strategy, genetic engineering has been increasingly demonstrated to act as an effective and efficient approach to generate transgenic plants with improved stress tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…'Hyuganatsu' is an SI cultivar with a very low level of parthenocarpy (Miwa, 1951;Yamashita, 1978), resulting in seedy fruit that are contrary to consumer preference. Although similar attempts have previously been made to isolate genes homologous to Rosaceae, Solanaceae, and Plantaginaceae S-RNases from some Citrus species (Chai et al, 2011;Liang et al, 2017;Miao et al, 2011), no confirmed S-RNases have been identified in citrus to date (Zhang et al, 2018). However, recent technological advances in DNA sequencing and successful completion of citrus genome sequencing projects have resulted in the public availability of annotated genome sequences of several citrus species (Shimizu et al, 2017;Wu et al, 2014;Xu et al, 2013) that will facilitate the identification of homologous genes.…”
Section: Introductionmentioning
confidence: 99%
“…Most citrus cultivars reproduce by sexual hybridization, frequent somatic mutation, and nucellar polyembryony; the latter is a feature of citrus in which the nucellar tissue that surrounds the embryonic sac containing the zygotic embryo develops one or more embryos that have the same genetic constitution as the maternal tissue cells [32,[51][52][53]. Satsuma mandarin cultivars have been particularly difficult to improve through hybridization because of polyembryony and male sterility [3,54].…”
Section: Discussionmentioning
confidence: 99%
“…Satsuma mandarin cultivars have been particularly difficult to improve through hybridization because of polyembryony and male sterility [3,54]. Accordingly, satsuma mandarin cultivars are bred by asexual methods, such as nucellar embryos [4,53] and bud mutation [3,6], and therefore have the same genetic and morphological traits as the mother plant [4]. 'Haryejosaeng' was developed from nucellar seedlings [4] of satsuma mandarin ('Tachima wase'), and it shows higher total soluble solids, and lower acidity than the most common satsuma mandarin ('Miyagawa wase') cultivated on farms [2] and has longer juvenile stages [55].…”
Section: Discussionmentioning
confidence: 99%